Analisis Penyebab dan Penyelesaian Penerimaan SP2DK CV LDM - Suci Rohmatul Rizky; Muslimin (Economic Reviews Journal, 2025)
Taxes are payments made by citizens to the government in accordance with the prevailing regulations. The tax imposition system in Indonesia now uses a self-assessment system, where taxpayers are given the authority to determine the amount of tax. This study aims to analyze the causes and solution for the receipt of SP2DK to CV LDM. The research applies a quantitative approach in the context of a case study and data collection techniques through interviews and direct observation. The result of the study indicate that CV LDM made an error in registering the company’s tax rate, which led to CV LDM receiving an SP2DK from the Account Representative (AR). CV LDM responded to the SP2DK with adequate evidence, and the Account Representative (AR) confirmed receipt of the response by issuing an Official Report.